Sentiment Analysis of User Satisfaction with Access by KAI Application Using Support Vector Machine and Random Forest Algorithms - Kurnia Gusti Ayu (Faculty of Engineering and Informatics, Universitas Multimedia Nusantara, 2026)
PT Kereta Api Indonesia (Persero), a State-Owned Enterprise (SOE) in the railway sector, holds an important responsibility in providing efficient services. To enhance their services, they introduced the application